Metabolomic Profiling and Biological Activities of Cell-Free Supernatants of Bacillus sp. Isolates: Antibacterial, Antibiofilm, and Anti-quorum Sensing Activities - Müjde Eryılmaz; Engin Koçak; Emirhan Nemutlu; Nurnehir Baltacı Bozkurt; Ekrem Murat Gönülalan; Gamze Benli Yardımcı (Experimed, 2024)
Objective: The objective of this research was to explore the antibacterial, antibiofilm, and anti-quorum sensing (anti-QS) activities of cellfree supernatants (CFSs) of Bacillus sp. and correlate these activities with their metabolite profiles.Materials and Methods: We used 55 Bacillus sp. isolates from soil samples. The antibacterial activities of the CFSs were investigated using disk diffusion and agar well diffusion methods. Antibiofilm activities were assessed using the crystal violet microplate method and anti-QS activities were evaluated using the disc diffusion method. The identification of biologically active isolates was performed using matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF-MS). The metabolite profiles of active CFSs were analyzed using gas chromatography-mass spectrometry (GC-MS).Results: Only S-45 exhibited antibacterial activity against Staphylococcus aureus ATCC 25923. Biofilm inhibition percentages of the CFSs against Staphylococcus epidermidis ATCC 35984 and Pseudomonas aeruginosa PAO1 varied between 92.58% - 3.96% and 78.96% - 0.64%, respectively. Only S-37 exhibited anti-QS activity. The most biologically active isolates belonged to the Bacillus cereus group. Based on the GC-MS results, 102 metabolites were identified. According to correlation analyses between the results of antibiofilm activity and metabolite profiles, we determined that compounds belonging to the amino acid and peptide groups, hydroxy acids and derivatives, and fatty acyls exhibited a highly positive correlation. The metabolite profiles of S-45 and S-37 were not significantly different from the negative control (S-46). Therefore, these activities could not be associated with the metabolite content.Conclusion: The correlation between specific metabolite profiles and bioactivities indicates the potential of these bioactivities for innovative pharmaceutical applications. Future research should focus on isolating and testing these individual metabolites to confirm their specific roles and mechanisms.